Acoustic-Based Screening Method for the Detection of Total Aflatoxin in Corn and Biological Detoxification in Bioethanol Production - Juodeikiene, Grazina; Cernauskas, Darius; Trakselyte-Rupsiene, Karolina; Bartkiene, Elena; Zadeike, Daiva; Banyte, Greta; Santini, Antonello (Frontiers in Microbiology, 2020)
Aspergillus spp. are widely occurring fungi in nature, producing toxic compounds such as aflatoxins (AFs), and mainly target plant products such as corn and nuts. The development of prevention strategies is challenging because AFs are highly toxic and have been regulated to small concentrations. This study proposes a new strategy of AF prevention by application of rapid methods using acoustic techniques in combination with fermentation for the elimination of contaminated corn from bioethanol production processes. The acoustic device was used for the analysis of model systems of corn and nuts (hazelnuts and peanuts) contaminated with different amounts of AFs. High correlations were obtained between penetrated acoustic signal amplitude (Ap) and corn sample density, and between Ap and AFs content. Also, relationships were found between changes in Ap values and AFs contamination in the nuts model systems. The results of biotreatment of contaminated corn during bioethanol production confirmed that AFs cannot be completely eliminated in dried distiller’s grains with solubles, a valuable by-product for animal feed. Microbially contamination of the raw material has a negative impact on bioethanol quality by increasing the content of volatile compounds. Therefore, the application of methods such as acoustic screening is a promising alternative for rapid AF detection in corn and nuts (it can handle multi-layers of grain). With the application of acoustic techniques, the prevention of AFs in contaminated raw plant materials could be achieved.